Pengaruh Motivasi Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan PT. Chang Shin Indonesia - Rohayat Rohayat; Enjang Suherman; Flora Patricia Anggela (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this research is to examine how the influence of discipline and work motivation on work productivity. This study uses a quantitative methodology which includes descriptive and verification analysis. The analytical method used is multiple regression. The population of this research is the employees of Pt. Chang Shin Indonesia from lean production with a workforce of 450 people. By collecting 60 respondents, the sample for this study was randomly selected. data collected through a questionnaire. To draw conclusions and test the hypothesis used descriptive analysis, verification and multiple regression. The t, R and F tests were used. The results of this study found that (1) the labor productivity of PT. Chang Shin Indonesia is partly influenced by work motivation. (2) Labor productivity of employees of PT. Chang Shin Indonesia is partly influenced by labor discipline. (3) Discipline and work motivation affect the work productivity of employees of PT. Chang-Shin Indonesia at the same time. Keyword : Work Motivation, Work Discipline, Work Produktivity